Avner Offer (1944–) - Getzler, J (Palgrave Macmillan, 2021)
Avner Offer’s work includes the history of property politics in England before the Great War; the impact of the international food economy on politics and strategy in Britain, the British Empire and Germany before and during that War; analysis of the experience of affluence and its impact on social mores and well-being in the United Kingdom and the United States since 1950; and a study of abstract economic theory and its influence on political ideologies and economic organisation in the West since the late 1960s. In his model building, he sees motivation through the lens of a quest for self-esteem and approbation and views institutions as devices to control and constrain commitment across time. Much of his work can be read as a defence of social democracy, and an analysis of how welfare can be destroyed by political and economic calculations inducing inequality and conflict.